Penerapan model pembelajaran think pair share berbantu media audio visual terhadap kemampuan menyimak cerita rakyat berbahasa jawa pada siswa kelas VII A SMP N 5 Pati - Rahmawati, Rizka Auliya; Sunarya, Sunarya; Zaidah, Nuning (Universitas PGRI Semarang, 2023)
This research aims to describe the results of application the Think Pair Share learning model on the ability to listen to Javanese folklore in class VII A students of SMP N 5 Pati. This research was motivated by the low ability of class VII students to listen to stories and the use of inappropriate learning methods or models so that learning became boring. The design of this research is pre-experimental in the form of a one-shot case study using only one class without a control or comparison group. The sampling technique used in this research was purposive sampling. The approach used in this research is quantitative descriptive. The data in this research was obtained by observation and through questionnaires. Meanwhile, the data collection technique in this research uses test techniques. The research results obtained after data analysis were carried out as follows: the research results explained that in the knowledge aspect there were 29 students or 85% who had reached the KKM, while 5 students or 28% had not reached the KKM, with a class average score of 81,98. In the skills aspect, there were 30 students or 88% who reached the KKM, while 4 students or 12% had not yet reached the KKM, with a class average score of 82,08. Thus, the application of the TPS (Think Pair Share) learning model to the ability to listen to Javanese folklore in class VII A students of SMP N 5 Pati can have an influence on learning achievement.